The Prevalence of Parasitic Infection in Domestic Chicken: A Review (Medico Legal Update, 2020)
The relative contribution of poultry to total animal protein production in the world is increasing, the major increase in developing countries. Many types and species of ectoparasites and Endoparasites are known to infect chickens; one of the actual problems that cause economic bias in animal farms and rural areas that raise chickens annually is parasitic diseases. The common parasitic infections that occur in poultry can divided to External parasites include arthropods Lice ,Mites, Fleas and Ticks which isolated from skin and feathers Internal parasites include protozoa ,cestodes, nematodes, trematodes which isolated from digestive tract, blood and Pooled poultry droppings. The external and internal parasites that infected hosts possess features such as small size, cylindrical body, hook and hard body, enhance their adaptation to the long life and effect on the poultry industry by affecting the growth rate of chickens, leading to little eggs production, and death in severe infections. Prevalence of helminthic infection (cestodes and nematodes infect by digestive tract) was highly in farms and rural areas chickens from the different studies in different sites in the world, followed by protozoa infection by blood, followed by arthropodic infection by skin and feathers and followed by prevalence by trematodes